Strategic model of creative thinking to produce narrative texts: tales in the fourth grade of primary – Lambayeque - Sandoval Damián, Virginia María (2017)
The present research denominated "Strategic model of creative thought to produce narrative texts: stories in fourth grade of primary - Lambayeque", was realized with the objective of proposing a strategic model of creative thought to produce stories in fourth grade of primary of IE 10132 Jesus Divine Master - Mochumí. In order to formalize the research, the IE director's authorization was requested, in which he provided the facilities to evaluate the level of text production, in the selected sample of 96 students. The results of the evaluation indicate that only 14% of the students in the four sections are planning in the dimension of planning by grade when planning a text, also as it is observed in the present study, in the dimension of textualization only 35% of the students apply the processes of textualization for the correct elaboration of a text. Finally, it is recommended that the director and teachers of EI No. 10132 Jesus Divine Master of Mochumí give greater emphasis on the strategic model of creative thinking through internal policies and meaningful learning sessions that contributes to raising the production of narrative texts and reading comprehension.